Intervensi Amerikat Serikat dalam Perjuangan Kemerdekaan Indonesia - Tangkilisan, Yuda B. (UI Scholars Hub, 2003)
This research deals with the relation between Indonesia dan the United States of America (US) in the past. Recently the role of the US becomes stronger and dominant in the international scene. The US also interferes into the foreign policy making of a country, like Indonesia. The single super powerm after the dismiss of the Uni-Sovyet following the end of the Cold War, imposed its will to Indonesia to take a part in a war against terrorism after the Tragedy 911. It seems that such a attitude is not something new happening in this era. The intervention already occurred in the past. The US got involved and interferred the Indonesian struggle for independence. On the one hand the conduct could be seen as a blessing in disguise because it forced Dutch to end its effort restoring a colonial rule. On the other, the US treated Indonesia not always friendly and sincerely. They pushed Indonesia to accept agreements with the Dutch to end the dispute.